Blogs for language teachers' development - Musayeva-Vefali, Gülşen; Tuncergil, Ciğdem (Nova Science Publishers, Inc., 2014)
Over the past decade, various aspects of computer-mediated communication (CMC) for professional development opportunities have been investigated. However, so far, few blogs have been launched for teacher development purposes (Eastment, 2005). In the present project, therefore, we initiated a blog with practicing English language teachers at a tertiary institution in Northern Cyprus. Content analysis and interpretation of the blog entries manifested that the endeavor provided the bloggers a medium for engagement in professional interaction, reflection, and inquiry, thus suggesting the blog's potential to benefit language teachers in terms of "becoming aware, autonomous, and authentic professionals" (van Lier, 1996, p. 225). © 2014 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Computer-mediated communication (CMC); Narrative blogs; Teacher professional development